Effect of environmental conditions and preventive behaviors on cutaneous leishmaniasis from the earthquake that hit cities in Western Iran in 2021: A cross-sectional study - Fakhreddin CHABOKSAVAR; Arash ZIAPOUR; Mozhgan IRANDOST; Behzad MAHAKI; Francesco CHIRICO; Murat YILDIRIM; Gabriella NUCERA; Lukasz SZARPAK; Nicola BRAGAZZI; Anvar ASADI (Journal of Health and Social Sciences)
Introduction: To investigate the role of environmental conditions, knowledge, attitudes, and control measures of preventive behaviors in cutaneous leishmaniasis (CL) based on the BASNEF model in patients who were referred to the health care centers of cities hit by earthquakes, including Sarpol-Zahab and Qasr-Shirin located in Kermanshah province, Western Iran, in 2021. Method: In this descriptive cross-sectional study, 128 individuals who visited rural and urban health centers were randomly selected, then they were asked to fill in a structured questionnaire with questions about their demographic information, environmental conditions, knowledge, attitude, and preventive behavior regarding CL. Results: Approximately 89.1% of the individuals used urban water supply networks, while 68% of the participants had access to the wastewater collection system. The most influential people in preventive behaviors (control actions) were family members (72.4%). Pearson’s correlation test showed that preventive behaviors positively correlated with understudy variables in the BASNEF model (p<0.001). Finally, enabling factors and behavioral intention were the most accurate predictors of preventive behaviors against CL. Conclusion: A combination of environmental, ecological conditions, and behavioral and sanitation factors may influence the distribution of causes of CL. Therefore, control programs should focus on villages and cities with high disease risks.